Optical laminate with surface protective film
By adjusting the surface resistivity on the release liner of the optical laminate and the surface of the surface protective film, and designing appropriate water contact angle and bonding strength at the contact point of the anti-fouling layer and the surface protective film, the problem of poor picking of the optical laminate during the picking process is solved, and higher picking accuracy and touch operability are achieved.
Patent Information
- Application Number
- CN202411474409.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-26
- Filing Date
- 2024-10-22
- Publication Date
- 2025-04-29
AI Technical Summary
The existing optical laminates are prone to picking defects during the picking process, especially because the adhesion between the release liner and the surface protective film is enhanced due to static electricity, resulting in the incorrect pickup or peeling of the optical laminate or the surface protective film.
The surface resistivity is adjusted on the release liner of the optical laminate and the surface protective film to be 1.0×1013Ω/□ or less, and the water contact angle is 100° or more and the adhesion strength is 0.07N/50mm or less at the contact point of the anti-fouling layer and the surface protective film to reduce the adhesion between the optical laminate.
The occurrence of pickup defects is effectively suppressed, and the pickup accuracy of the optical laminated body and the operability of the touch panel are improved.
Smart Images

Figure CN119899596A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an optical laminate with a surface protection film. Background Art
[0002] Anti-reflection films disposed on the outermost surface of image display devices, films for detecting positions of touch panels, window films attached to window glass and display windows, etc. are used in a state where they can be touched from the outside, and are therefore easily affected by contamination caused by fingerprints, hand dirt, dust, etc. Therefore, an anti-fouling layer is provided for the purpose of easily preventing contamination from the external environment and easily removing attached contaminants.
[0003] In order to prevent damage and contamination in the state before use during processing and transportation, etc., a surface protective film is temporarily bonded to these optical films (optical laminates) (for example, see Patent Document 1). Hereinafter, the optical laminate to which the surface protective film is temporarily bonded is sometimes referred to as an "optical laminate with a surface protective film" or simply referred to as an "optical laminate".
[0004] In the optical laminate with a surface protective film (laminated plastic film for optical filter) described in Patent Document 1, an adhesive layer and a release film (release liner) are sequentially laminated on the surface opposite to the surface protective film. The release liner protects the adhesive layer until the optical laminate is attached to an adherend (e.g., an image display panel, etc.). Therefore, in the optical laminate described in Patent Document 1, one main surface is the surface of the surface protective film, and the other main surface is the surface of the release liner until the optical laminate is attached to the adherend.
[0005] On the other hand, when the optical stack is attached to an image display panel, etc., for example, a process of picking up one by one from a plurality of stacked optical stacks using an adsorption fixture is provided. At this time, due to static electricity, there is a tendency for the release liner of the first optical stack to be easily fitted with the surface protective film of the second optical stack. If the adhesion between the release liner and the surface protective film becomes stronger, when picking up the first optical stack, the second optical stack is sometimes picked up together, or the surface protective film is peeled off from the second optical stack. Hereinafter, the above-mentioned undesirable conditions during the picking-up process of the optical stack are sometimes recorded as "poor picking up". In particular, in an optical stack having an antifouling layer directly below the surface protective film, in terms of the properties of the antifouling layer that is easy to repel moisture and oil, there is a tendency that the adhesion between the antifouling layer and the surface protective film becomes low, and the surface protective film is easily peeled off from the antifouling layer. It is difficult to suppress the occurrence of poor picking up using only the technology described in Patent Document 1.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2008-151996 Summary of the invention
[0009] The present invention has been made in view of the above-mentioned circumstances, and an object of the present invention is to provide an optical laminate with a surface protection film which can suppress the occurrence of pickup failure.
[0010] <Aspects of the present invention>
[0011] The present invention includes the following aspects.
[0012] [1] An optical laminate with a surface protective film, comprising, in order, a release liner, an adhesive layer, a transparent film substrate, an antifouling layer, and a surface protective film, wherein the principal surface of the release liner on the side opposite to the adhesive layer is a first principal surface of the optical laminate with a surface protective film, the principal surface of the surface protective film on the side opposite to the antifouling layer is a second principal surface of the optical laminate with a surface protective film, and the surface resistivity of the first principal surface and the second principal surface of the optical laminate with a surface protective film is both 1.0×10 13 Ω / □ or less.
[0013] [2] The optical laminate with a surface protection film according to [1], wherein the antifouling layer is in contact with the surface protection film, and the water contact angle of the main surface of the antifouling layer on the surface protection film side is 100° or more.
[0014] [3] The optical laminate with a surface protection film according to [1] or [2], wherein the antifouling layer is in contact with the surface protection film, and the adhesion strength between the antifouling layer and the surface protection film is 0.07 N / 50 mm or less.
[0015] [4] The optical laminate with a surface protection film according to any one of [1] to [3], wherein the surface resistivity of the second main surface of the optical laminate with a surface protection film is 1.0×10 8 Ω / □ or more.
[0016] [5] An optical laminate with a surface protection film according to any one of [1] to [4], wherein the transparent film substrate comprises a transparent film and a hard coating layer provided on a first main surface side of the transparent film, and the adhesive layer is provided on a second main surface side of the transparent film.
[0017] [6] The optical laminate with a surface protection film according to any one of [1] to [5], further comprising an antireflection layer provided between the transparent film substrate and the antifouling layer.
[0018] [7] The optical laminate with a surface protection film according to [6], further comprising a primer layer provided between the transparent film substrate and the antireflection layer.
[0019] Effects of the Invention
[0020] According to the present invention, an optical layered body with a surface protection film capable of suppressing occurrence of pickup failure can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a cross-sectional view showing an example of the optical laminate with a surface protection film of the present invention.
[0022] Figure 2 This is a cross-sectional view for explaining a method for evaluating the pickup properties of an optical laminate with a surface protection film.
[0023] Description of reference numerals:
[0024] 10: optical laminate; 11: release liner; 12: adhesive layer; 13: transparent film substrate; 14: antifouling layer; 15: surface protection film; 18: transparent film; 19: hard coating layer; 20: antireflection layer; 25: primer layer. DETAILED DESCRIPTION
[0025] Hereinafter, preferred embodiments of the present invention will be described in detail, but the present invention is not limited thereto. In addition, all of the academic documents and patent documents described in this specification are cited as references in this specification.
[0026] First, the terms used in this specification are explained. "Refractive index" is the refractive index of light with a wavelength of 550nm in an atmosphere with a temperature of 23°C. "Standard environment" refers to an environment with a temperature of 23°C and a relative humidity of 50%. The "principal surface" of a layered object (more specifically, a release liner, an adhesive layer, a transparent film substrate, an antifouling layer, a surface protective film, a transparent film, a hard coating layer, a primer layer, an antireflection layer, a substrate layer, an adhesive layer, an optical laminate with a surface protective film, etc.) refers to the surface of the layered object that is orthogonal to the thickness direction. The "first principal surface" of a layered object refers to one of the two principal surfaces of the layered object. The "second principal surface" of a layered object refers to the principal surface of the layered object on the opposite side of the first principal surface.
[0027] Unless otherwise specified, the numerical value of the "thickness (film thickness)" of a layered material is as follows: observing a cross section of the layered material cut along the thickness direction using an electron microscope, randomly selecting 10 measurement locations from the cross-sectional image, and measuring the thickness of the selected 10 measurement locations to obtain the arithmetic mean of the 10 measurement values.
[0028] Unless otherwise specified, the number average primary particle size of the particles is the following value: the number average value of the equivalent circle diameter (Heywood diameter: the diameter of a circle having the same area as the projected area of the primary particles) of 100 primary particles measured using a scanning electron microscope and image processing software (e.g., "ImageJ" manufactured by the National Institutes of Health).
[0029] In the following, "system" is sometimes added after the compound name to collectively refer to the compound and its derivatives. In addition, when "system" is added after the compound name to indicate the name of a polymer, unless otherwise specified, it means that the repeating unit of the polymer is derived from the compound or its derivatives. In addition, acrylic acid and methacrylic acid are sometimes collectively referred to as "(meth)acrylic acid".
[0030] The components, functional groups, and the like exemplified in the present specification may be used alone or in combination of two or more unless otherwise specified.
[0031] In the following description, the drawings referred to are mainly schematically shown for easy understanding, and the size, number, shape, etc. of the components shown in the drawings are sometimes different from the actual ones for the convenience of making the drawings. In addition, for the convenience of explanation, in the drawings described later, the same reference numerals are sometimes given to the same components as those in the drawings described previously, and their descriptions are omitted.
[0032] <Optical laminate with surface protection film>
[0033] The optical laminate with a surface protective film of the present embodiment (hereinafter sometimes referred to as "optical laminate A") comprises a release liner, an adhesive layer, a transparent film substrate, an antifouling layer, and a surface protective film in this order. The main surface of the release liner on the side opposite to the adhesive layer is the first main surface of the optical laminate A. The main surface of the surface protective film on the side opposite to the antifouling layer is the second main surface of the optical laminate A. The surface resistivity of the first main surface of the optical laminate A and the surface resistivity of the second main surface of the optical laminate A are both 1.0×10 13 Ω / □ or less.
[0034] The "surface resistivity" is measured by the same method as the measuring method in Examples described later or a method based on the method.
[0035] According to the optical layered body A, since it has the above-mentioned structure, it is possible to suppress the occurrence of pickup failure. The reason is presumably as follows.
[0036] In the optical laminate A, the surface resistivity of the main surface on the release liner side (first main surface) and the main surface on the surface protection film side (second main surface) were both 1.0×10 13Ω / □ or less, so that the two main surfaces of the optical stack A are suppressed from being charged. Therefore, in the picking-up process, when picking up one by one from the stacked multiple optical stacks A, there is a tendency for the adhesion between the optical stacks A (specifically, the release liner of one optical stack A and the surface protective film of the other optical stack A) to decrease. Therefore, when picking up the optical stacks A one by one, the adhesion of the release liner to the surface protective film is suppressed, so according to the optical stack A, the occurrence of picking defects can be suppressed.
[0037] In the present embodiment, in order to further suppress the occurrence of pickup failure, the surface resistivity of the first main surface of the optical stack A and the surface resistivity of the second main surface of the optical stack A are both preferably 9.0×10 12 Ω / □ or less, more preferably 7.0×10 12 Ω / □ or less, more preferably 5.0×10 12 Ω / □ or less. It should be noted that the surface resistivity of the first main surface of the optical layered body A and the surface resistivity of the second main surface of the optical layered body A may be the same value or different values.
[0038] The lower limit of the surface resistivity of the first main surface (surface of the release liner) of the optical layered body A is not particularly limited, but is preferably 1.0×10 7 Ω / □ or more, more preferably 1.0×10 8 Ω / □ or more.
[0039] When the optical laminate A is used as an optical film (such as an antireflection film, etc.) attached to the surface of the image display panel, after peeling off the release liner from the optical laminate A, the exposed adhesive layer is attached to the surface of the image display panel. In the manufacture of the image display device, with respect to the optical laminate A attached to the surface of the image display panel (in detail, the optical laminate A after peeling off the release liner), the surface protective film is usually the outermost layer of the optical laminate A. In this case, in the inspection process of the image display device, when confirming the operability of the touch panel, the surface of the surface protective film (the second main surface of the optical laminate A) is confirmed with a finger touch. At this time, if the surface resistivity of the second main surface of the optical laminate A is too low, sometimes it is difficult to produce a reaction even if the screen is touched with a finger (in detail, the second main surface of the optical laminate A). Below, when confirming the operability of the touch panel, sometimes the phenomenon that the screen does not react or is difficult to react even if the screen is touched with a finger is recorded as a "touch panel sensor error".
[0040] In order to suppress the occurrence of touch panel sensor errors, the surface resistivity of the second main surface of the optical laminate A is preferably 1.0×10 8 Ω / □ or more, more preferably 1.0×109 Ω / □ or more, more preferably 1.5×10 9 Ω / □ or more.
[0041] The surface resistivity of the first and second main surfaces of the optical layered body A can be adjusted, for example, by antistatic treatment. Examples of the active ingredient of the treatment agent for antistatic treatment include one or more selected from the group consisting of antistatic agents and conductive polymers.
[0042] When an antistatic agent is used, the antistatic treatment is performed by the following method: for example, after diluting the antistatic agent with a solvent (specifically, an organic solvent, water, etc.) as needed, it is applied to the treated surface (specifically, the surface of the release liner that becomes the first main surface of the optical laminate A, or the surface of the surface protective film that becomes the second main surface of the optical laminate A) and dried. When the antistatic agent is used for treatment, the surface resistivity of the treated surface can be adjusted by changing at least one of the type and amount of the antistatic agent used. As the antistatic agent, for example, a polymer containing a quaternary ammonium cation, a polyaniline sulfonic acid antistatic agent, a phosphate antistatic agent, etc. can be listed, preferably a polymer containing a quaternary ammonium cation.
[0043] In the case of using a conductive polymer, the antistatic treatment is performed, for example, by applying a treatment agent containing a conductive polymer to the treated surface (specifically, the surface of the film substrate constituting the release liner or the surface of the film substrate constituting the surface protective film) and drying. The surface of the layer containing the conductive polymer formed by the antistatic treatment is the first main surface or the second main surface of the optical laminate A. When the treatment agent containing a conductive polymer is used, the surface resistivity of the first main surface or the second main surface of the optical laminate A can be adjusted by changing at least one of the type and amount of the conductive polymer used. In order to adjust the surface resistivity to the above-mentioned preferred range, the thickness of the layer containing the conductive polymer is preferably 1 nm or more and 100 nm or less, and more preferably 3 nm or more and 50 nm or less.
[0044] As the conductive polymer, for example, polythiophene, polyaniline, polypyrrole, polyquinoxaline, polyacetylene, polyphenylene vinylene, polynaphthalene and derivatives thereof can be cited. The conductive polymer is preferably one or more selected from the group consisting of polythiophene, polyaniline and derivatives thereof, more preferably a polythiophene derivative, further preferably poly(3,4-disubstituted thiophene), further preferably poly(3,4-alkylenedioxythiophene), and particularly preferably poly(3,4-ethylenedioxythiophene).
[0045] The conductive polymer may have a hydrophilic functional group, such as a sulfone group, an amino group, an amide group, an imino group, a hydroxyl group, a mercapto group, a hydrazine group, a carboxyl group, a sulfate group, a phosphate group, a quaternary ammonium cation group, and salts thereof (such as a quaternary ammonium salt group).
[0046] As a dopant of the conductive polymer, for example, polyanions can be listed. When the conductive polymer is polythiophene or a derivative thereof, the polyanion can form an ion pair with the polythiophene or a derivative thereof. As the polyanion, there is no particular limitation, and for example, carboxylic acid polymer compounds such as polyacrylic acid, polymaleic acid, and polymethacrylic acid; sulfonic acid polymer compounds such as polystyrene sulfonic acid, polyvinyl sulfonic acid, and polyisoprene sulfonic acid can be listed. The polyanion can be a copolymer of a vinyl carboxylic acid monomer or a vinyl sulfonic acid monomer and other monomers. As examples of other monomers, (meth)acrylate compounds and aromatic vinyl compounds (specifically styrene, vinyl naphthalene, etc.) can be listed. The polyanion is preferably polystyrene sulfonic acid.
[0047] The treating agent containing the conductive polymer may contain components other than the conductive polymer and the dopant (other components). Examples of other components include: solvents (water, alcohol, etc.), adhesives (polyester resins, etc.), slip imparting agents (carnauba wax, etc.), crosslinking agents (melamine crosslinking agents, etc.), leveling agents, antioxidants, inorganic fillers, organic fillers, etc.
[0048] The following will describe the details of the optical laminate A with reference to the attached drawings as appropriate. Figure 1 Side description. Figure 1 It is a cross-sectional view showing an example of the optical layered body A (optical layered body 10 ).
[0049] Figure 1 The optical laminate 10 shown in the figure includes a release liner 11, an adhesive layer 12, a transparent film substrate 13, an antifouling layer 14, and a surface protective film 15 in this order. The main surface 11a of the release liner 11 opposite to the adhesive layer 12 side is the first main surface 10a of the optical laminate 10. The main surface 15a of the surface protective film 15 opposite to the antifouling layer 14 side is the second main surface 10b of the optical laminate 10. The surface resistivity of the first main surface 10a of the optical laminate 10 and the surface resistivity of the second main surface 10b of the optical laminate 10 are both 1.0×10 13 Ω / □ or less.
[0050] The surface protection film 15 includes a base layer 16 and an adhesive layer 17 laminated on the antifouling layer 14 side of the base layer 16. The surface protection film 15 is bonded to the antifouling layer 14 via the adhesive layer 17 so as to be releasable.
[0051] The transparent film substrate 13 includes a transparent film 18 and a hard coating layer 19 provided on the first main surface 18a side of the transparent film 18. The adhesive layer 12 is provided on the second main surface 18b side of the transparent film 18.
[0052] The optical laminate 10 includes an antireflection layer 20 between the transparent film substrate 13 and the antifouling layer 14. The optical laminate 10 includes a primer layer 25 between the transparent film substrate 13 and the antireflection layer 20. The optical laminate 10 functions as an antireflection film by being bonded to the surface of an image display panel (not shown), for example.
[0053] Anti-reflection layer 20 has these four layers of high refractive index layer 21, low refractive index layer 22, high refractive index layer 23 and low refractive index layer 24 successively from primer layer 25 sides.Details about high refractive index layer and low refractive index layer are described later.It should be noted that anti-reflection layer is not limited to such four layers of anti-reflection layer 20 formations, can also be two-layer formation, three-layer formation, five-layer formation or six-layer stacking formations.Anti-reflection layer is preferably the alternating laminate of the high refractive index layer more than two layers and the low refractive index layer more than two layers.In order to reduce the reflection on the air surface, the preferred outermost layer (the layer farthest from primer layer) of anti-reflection layer is a low refractive index layer.
[0054] When the optical laminate 10 is used (after the surface protection film 15 is peeled off from the antifouling layer 14), in order to improve the antifouling performance of the antifouling layer 14, the water contact angle of the main surface 14a on the surface protection film 15 side of the antifouling layer 14 is preferably 100° or more, more preferably 105° or more, further preferably 110° or more, further preferably 115° or more, and can be 116° or more, 117° or more, or 118° or more. The method for measuring the water contact angle is the same method as the measuring method of the embodiment described later or a method based on the method. The water contact angle of the main surface 14a on the surface protection film 15 side of the antifouling layer 14 can be adjusted by, for example, changing at least one of the type of material constituting the antifouling layer 14 and the thickness of the antifouling layer 14.
[0055] like Figure 1As shown, when the antifouling layer 14 is in contact with the surface protection film 15, if the water contact angle of the main surface 14a on the surface protection film 15 side of the antifouling layer 14 is 100° or more, the adhesion between the antifouling layer 14 and the surface protection film 15 is usually reduced, and there is a tendency to easily produce poor pickup. However, in this embodiment, as described above, since there is a tendency for the adhesion between the optical laminates to decrease, even if the water contact angle of the main surface 14a on the surface protection film 15 side of the antifouling layer 14 is 100° or more, 105° or more, 110° or more, 115° or more, 116° or more, 117° or more, or 118° or more, it is possible to suppress poor pickup. In order to further suppress poor pickup, the water contact angle of the main surface 14a on the surface protection film 15 side of the antifouling layer 14 is preferably 125° or less, and more preferably 120° or less.
[0056] In addition, if Figure 1 As shown, when the antifouling layer 14 is connected to the surface protection film 15, if the adhesion strength of the antifouling layer 14 and the surface protection film 15 becomes small, there is usually a tendency that poor pickup is easy to produce. However, in the present embodiment, as described above, due to the tendency that the adhesion between the optical laminates is reduced, even if the adhesion strength of the antifouling layer 14 and the surface protection film 15 is 0.07N / 50mm or less, 0.06N / 50mm or less, 0.05N / 50mm or less, 0.04N / 50mm or less or 0.03N / 50mm or less, it is also possible to suppress poor pickup. In order to further suppress poor pickup, the adhesion strength of the antifouling layer 14 and the surface protection film 15 is preferably more than 0.01N / 50mm. The adhesion strength of the antifouling layer 14 and the surface protection film 15 can be adjusted, for example, by changing at least one of the types of materials constituting the antifouling layer 14 and the thickness of the antifouling layer 14. The method for measuring the adhesion strength is the same method as the measuring method in Examples described later or a method based on this method.
[0057] It should be noted that Figure 1 In the example shown, the transparent film substrate has a hard coating layer, but the transparent film substrate that can be used in the present invention is not limited to the above example. For example, the transparent film substrate that can be used in the present invention may not have a hard coating layer. In the case where the transparent film substrate does not have a hard coating layer, as the transparent film substrate, for example, a transparent film ( Figure 1 In the example shown, this is a transparent film 18 ).
[0058] Next, each layer included in the optical layered body 10 will be described in detail.
[0059] [Release liner 11]
[0060] The release liner 11 protects the surface of the adhesive layer 12, for example, until the optical laminate 10 is attached to an adherend (not shown). As the constituent material of the release liner 11, a plastic film formed of acrylic acid, polyolefin, cyclic polyolefin, polyester, etc. is preferably used. The release liner 11 can be a laminate of more than two layers. In the case where the release liner 11 is a laminate of more than two layers, for example, the release liner 11 can be a laminate having a film substrate and the above-mentioned layer containing a conductive polymer. As a film substrate provided with a layer containing a conductive polymer, a plastic film formed of the material exemplified as the constituent material of the above-mentioned release liner 11 is preferably used. The thickness of the release liner 11 is, for example, not less than 5 μm and not more than 200 μm. The main surface of the adhesive layer 12 side of the release liner 11 is preferably subjected to a release treatment. As the material of the release treatment agent used for the release treatment, silicone materials, fluorine materials, long-chain alkyl materials, fatty acid amide materials, etc. can be listed.
[0061] [Adhesive layer 12]
[0062] The adhesive (pressure-sensitive adhesive) constituting the adhesive layer 12 is not particularly limited. For example, a transparent adhesive having a base polymer such as acrylic polymer, silicone polymer, polyester, polyurethane, polyamide, polyvinyl ether, vinyl acetate-vinyl chloride copolymer, modified polyolefin, epoxy resin, fluorine resin, natural rubber, synthetic rubber, etc. can be appropriately selected and used. The thickness of the adhesive layer 12 is not particularly limited. From the viewpoint of both thinness and adhesiveness, it is preferably 5 μm or more and 100 μm or less.
[0063] [Transparent film 18]
[0064] The transparent film 18 is, for example, a flexible transparent resin film. As the material constituting the transparent film 18, for example, polyester resin, polyolefin resin, polystyrene resin, acrylic resin, polycarbonate resin, polyethersulfone resin, polysulfone resin, polyamide resin, polyimide resin, cellulose resin, norbornene resin, polyarylate resin, and polyvinyl alcohol resin can be cited. As the polyester resin, for example, polyethylene terephthalate (PET), polybutylene terephthalate, and polyethylene naphthalate can be cited. As the polyolefin resin, for example, polyethylene, polypropylene, and cycloolefin polymer (COP) can be cited. As the cellulose resin, for example, triacetyl cellulose (TAC) can be cited. These materials can be used alone or in combination of two or more. As the material of the transparent film 18, from the viewpoint of transparency and strength, it is preferably selected from the group consisting of polyester resin, polyolefin resin, and cellulose resin, more preferably selected from the group consisting of PET, COP, and TAC, and further preferably TAC. That is, the transparent film 18 is preferably a film selected from the group consisting of polyester resin films, polyolefin resin films, and cellulose resin films, more preferably a film selected from the group consisting of PET films, COP films, and TAC films, and even more preferably a TAC film.
[0065] From the viewpoint of strength, the thickness of the transparent film 18 is preferably 5 μm or more, more preferably 10 μm or more, and further preferably 20 μm or more. From the viewpoint of handleability, the thickness of the transparent film 18 is preferably 300 μm or less, and more preferably 200 μm or less.
[0066] One or both main surfaces of the transparent film 18 may be subjected to a surface modification treatment. Examples of the surface modification treatment include corona treatment, plasma treatment, ozone treatment, primer treatment, glow treatment, and coupling agent treatment.
[0067] From the viewpoint of improving the transparency of the optical layered body 10 , the total light transmittance (JIS K7375-2008) of the transparent film 18 is preferably 80% or more, more preferably 90% or more, and further preferably 95% or more and 100% or less.
[0068] [Hard coating 19]
[0069] The hard coating layer 19 is a layer that improves the mechanical properties of the optical laminate 10, such as the hardness and elastic modulus. The hard coating layer 19 is formed, for example, by a cured product of a curable resin composition (composition for forming a hard coating layer). Examples of the curable resin contained in the curable resin composition include polyester resins, acrylic resins, carbamate resins, carbamate acrylate resins, amide resins, silicone resins, epoxy resins, and melamine resins. These curable resins can be used alone or in combination of two or more. From the viewpoint of improving the hardness of the hard coating layer 19, the curable resin is preferably selected from one or more of the group consisting of acrylic resins and carbamate acrylate resins, and more preferably a carbamate acrylate resin.
[0070] In addition, as a curable resin composition, for example, a UV-curable resin composition and a thermosetting resin composition can be listed. From the viewpoint of improving the productivity of the optical laminate 10, as a curable resin composition, a UV-curable resin composition is preferably used. The UV-curable resin composition contains one or more selected from the group consisting of a UV-curable monomer, a UV-curable oligomer, and a UV-curable polymer. As a specific example of a UV-curable resin composition, a hard coat forming composition described in Japanese Patent Publication No. 2016-179686 can be listed.
[0071] In addition, the curable resin composition may contain microparticles. By adding microparticles to the curable resin composition, the hardness, surface roughness, refractive index and anti-glare properties of the hard coating layer 19 can be adjusted. As microparticles, for example, metal (or semi-metal) oxide particles, glass particles, and organic particles can be listed. As materials of metal (or semi-metal) oxide particles, for example, silicon dioxide, aluminum oxide, titanium dioxide, zirconium oxide, calcium oxide, tin oxide, indium oxide, cadmium oxide, and antimony oxide can be listed. As materials of organic particles, for example, polymethyl methacrylate, polystyrene, polyurethane, acrylic-styrene copolymer, benzoguanamine, melamine, and polycarbonate can be listed.
[0072] In addition, the curable resin composition may contain particles having a number average primary particle size of less than 1.0 μm (hereinafter sometimes referred to as "nanoparticles") as the above-mentioned microparticles. That is, the hard coating layer 19 may contain nanoparticles. In the case where the hard coating layer 19 is formed by a cured product of a curable resin composition containing nanoparticles, fine concavoconvexities are formed on the surface of the hard coating layer 19, and there is a tendency that the adhesion between the hard coating layer 19 and the layer formed thereon (e.g., the primer layer 25) is improved.
[0073] From the viewpoint of forming a fine concavo-convex shape contributing to improved adhesion, the number average primary particle size of the nanoparticles is preferably 20 nm to 80 nm, more preferably 25 nm to 70 nm, and even more preferably 30 nm to 60 nm.
[0074] As the material of the nanoparticles, inorganic oxides are preferred. As inorganic oxides, oxides of metals (or semi-metals) such as silicon oxide (silicon dioxide), titanium oxide, aluminum oxide, zirconium oxide, niobium oxide, zinc oxide, tin oxide, cerium oxide, and magnesium oxide can be cited. The inorganic oxide can be a composite oxide of multiple (semi) metals. Among the exemplified inorganic oxides, silicon oxide is preferred from the perspective of high adhesion improvement effect. That is, as nanoparticles, silicon oxide particles (silicon dioxide particles) are preferred. On the surface of the inorganic oxide particles as nanoparticles, functional groups such as acryloyl and epoxy groups can be introduced for the purpose of improving adhesion and affinity with the resin.
[0075] The amount of the nanoparticles in the hard coating 19 is preferably 5 parts by weight or more relative to 100 parts by weight of the curable resin, and can be 10 parts by weight or more, 20 parts by weight or more, or 30 parts by weight or more. If the amount of the nanoparticles is 5 parts by weight or more, the adhesion with the layer formed on the hard coating 19 can be further improved. The upper limit of the amount of the nanoparticles in the hard coating 19 is, for example, 90 parts by weight, preferably 80 parts by weight, and can be 70 parts by weight relative to 100 parts by weight of the curable resin.
[0076] From the viewpoint of improving the hardness of the hard coating layer 19, the thickness of the hard coating layer 19 is preferably 1 μm or more, more preferably 2 μm or more. From the viewpoint of ensuring the flexibility of the optical laminate 10, the thickness of the hard coating layer 19 is preferably 50 μm or less, more preferably 40 μm or less, further preferably 35 μm or less, and further preferably 30 μm or less.
[0077] The main surface of the hard coating layer 19 on the opposite side to the transparent film 18 side may be subjected to surface modification treatment. Examples of surface modification treatments include plasma treatment, corona treatment, ozone treatment, primer treatment, glow treatment, and coupling agent treatment. In order to improve the adhesion between the layer (e.g., primer layer 25 described later) provided on the opposite side to the transparent film 18 side of the hard coating layer 19 and the hard coating layer 19, the main surface of the hard coating layer 19 on the opposite side to the transparent film 18 side is preferably subjected to plasma treatment.
[0078] (Method for Forming Hard Coat Layer 19)
[0079] The hard coat layer 19 is formed, for example, by applying a curable resin composition (composition for forming a hard coat layer) on one main surface of the transparent film 18, removing the solvent and curing the resin as required. The composition for forming a hard coat layer contains, for example, the curable resin and a polymerization initiator (for example, a photopolymerization initiator) as described above, and contains, as required, a solvent that can dissolve or disperse these components.
[0080] In addition to the above-mentioned components, the hard coat forming composition may also contain additives such as nanoparticles, particles having a number average primary particle size of 1.0 μm or more, leveling agents, viscosity adjusters (thixotropic agents, thickeners, etc.), antistatic agents, anti-blocking agents, dispersants, dispersion stabilizers, antioxidants, ultraviolet absorbers, defoaming agents, surfactants, lubricants, etc.
[0081] As a coating method for the hard coat forming composition, any appropriate method such as rod coating, roller coating, gravure coating, rod coating, slot orifice coating, curtain coating, injection coating, notch wheel coating, etc. can be adopted. The drying temperature of the coating film after coating can be set to an appropriate temperature according to the composition of the hard coat forming composition, for example, above 50°C and below 150°C. In the case where the resin component in the hard coat forming composition is a thermosetting resin, the coating film is cured by heating. In the case where the resin component in the hard coat forming composition is a photocurable resin, the coating film is cured by irradiating active energy rays such as ultraviolet rays. The cumulative light amount of the irradiated light is preferably 100mJ / cm 2 Above and 500mJ / cm 2 the following.
[0082] [Primer layer 25]
[0083] In order to improve the adhesion between the transparent film substrate 13 (hard coating layer 19) and the anti-reflection layer 20, a primer layer 25 is preferably provided between the transparent film substrate 13 and the anti-reflection layer 20. Examples of the material of the primer layer 25 include metals (or semi-metals) such as silicon, nickel, chromium, tin, gold, silver, platinum, zinc, titanium, indium, tungsten, aluminum, zirconium, palladium, etc.; alloys of these metals (or semi-metals); oxides, fluorides, sulfides or nitrides of these metals (or semi-metals), etc. The oxide constituting the primer layer 25 may be a composite oxide such as indium tin oxide (ITO). Among them, the material of the primer layer 25 is preferably an inorganic oxide, more preferably silicon oxide, indium oxide or ITO, and further preferably SiOx (x<2).
[0084] In order to improve the adhesion between the transparent film substrate 13 and the antireflection layer 20 and ensure the light transmittance of the primer layer 25, the thickness of the primer layer 25 is preferably 0.5 nm to 20 nm, more preferably 0.5 nm to 10 nm, and further preferably 1.0 nm to 10 nm.
[0085] (Method for Forming Primer Layer 25)
[0086] The formation (film formation) method of the primer layer 25 is not particularly limited, and may be any of a wet coating method and a dry coating method. From the perspective of being able to form a thin film with uniform film thickness, a dry coating method such as a vacuum evaporation method, a CVD method, or a sputtering method is preferred. In addition, from the perspective of improving productivity, as a film formation method for the primer layer 25, a method of film formation using a roll-to-roll sputtering film forming device (roll-to-roll sputtering method) is preferred.
[0087] In the roll-to-roll sputtering method, a long film (e.g., a transparent film substrate 13) can be transported along the long dimension direction (MD direction) while continuously forming a film such as a primer layer 25 and an anti-reflection layer 20. In the sputtering method, film formation is performed while an inert gas such as argon and a reactive gas such as oxygen are introduced into the film forming chamber as needed. In the case of forming an oxide layer as the primer layer 25, the film formation of the oxide layer based on the sputtering method can be implemented by a method using an oxide target and a reactive sputtering method using a metal (or semi-metal) target.
[0088] Examples of power sources for sputtering include DC power sources, AC power sources, RF power sources, and MFAC power sources (AC power sources with a frequency band of several kHz to several MHz). The power density when sputtering is performed is, for example, 0.1 W / cm 2 Above and 20W / cm 2 Below, preferably 1W / cm 2 Above and 15W / cm 2 The surface temperature of the film forming roller during the sputtering method is, for example, not less than -25°C and not more than 25°C, preferably not less than -20°C and not more than 0°C. The pressure in the film forming chamber during the sputtering method is preferably not less than 0.01Pa and not more than 10Pa, more preferably not less than 0.05Pa and not more than 5Pa, and further preferably not less than 0.1Pa and not more than 1Pa.
[0089] [Anti-reflection layer 20]
[0090] The anti-reflection layer 20 is preferably formed of two or more thin films with different refractive indices. Generally, the anti-reflection layer adjusts the optical film thickness (the product of the refractive index and the thickness) of the thin film in such a way that the reversed phases of the incident light and the reflected light cancel each other. By making the anti-reflection layer a multilayer laminate of two or more thin films with different refractive indices, the reflectivity can be reduced in the wavelength range of a wide band of visible light.
[0091] Examples of the material of the thin film constituting the antireflection layer 20 include metal (or semimetal) oxides, nitrides, fluorides, etc. The antireflection layer 20 is preferably an alternating stack of high refractive index layers and low refractive index layers.
[0092] The refractive index of the high refractive index layer is, for example, 1.9 or more, preferably 2.0 or more. As the material of the high refractive index layer, titanium oxide, niobium oxide (Nb2O5, etc.), zirconium oxide, tantalum oxide, zinc oxide, indium oxide, ITO, antimony-doped tin oxide (ATO), etc. can be listed. Among them, it is preferably selected from one or more of the group consisting of titanium oxide and niobium oxide. The refractive index of the low refractive index layer is, for example, 1.6 or less, preferably 1.5 or less. As the material of the low refractive index layer, silicon oxide (SiO2, etc.), titanium nitride, magnesium fluoride, barium fluoride, calcium fluoride, hafnium fluoride, lanthanum fluoride, etc. can be listed. Among them, silicon oxide is preferred. It is particularly preferred to alternately stack a niobium oxide film as a high refractive index layer and a silicon oxide film as a low refractive index layer. In addition to the low refractive index layer and the high refractive index layer, a medium refractive index layer having a refractive index greater than 1.6 and less than 1.9 can also be provided.
[0093] The film thickness of high refractive index layer and low refractive index layer is preferably more than 5nm and below 200nm respectively, more preferably more than 10nm and below 150nm.According to refractive index, stacking formation etc., the film thickness of each layer is designed in a way that the reflectivity of visible light tapers down.For example, as the stacking formation of high refractive index layer and low refractive index layer, can list: from hard coat 19 sides by optical film thickness more than 20nm and the high refractive index layer below 55nm, optical film thickness more than 25nm and the low refractive index layer below 55nm, optical film thickness more than 80nm and the high refractive index layer below 250nm and the optical film thickness more than 100nm and the low refractive index layer below 150nm constitute four layers of formation.
[0094] In the case where the antireflection layer 20 is a four-layer alternating stacked body in which a niobium oxide thin film as a high refractive index layer and a silicon oxide thin film as a low refractive index layer are alternately stacked, the antireflection layer 20 may include, in order from the hard coating layer 19 side, a niobium oxide thin film having a thickness of 5 nm to 20 nm, a silicon oxide thin film having a thickness of 10 nm to 40 nm, a niobium oxide thin film having a thickness of 65 nm to 120 nm, and a silicon oxide thin film having a thickness of 60 nm to 100 nm.
[0095] In order to obtain an anti-reflection layer 20 having excellent bending resistance, the thickness of the anti-reflection layer 20 is preferably 140 nm to 280 nm, more preferably 170 nm to 280 nm, further preferably 180 nm to 260 nm, and further preferably 190 nm to 250 nm. It should be noted that in this specification, the "thickness of the anti-reflection layer" is the sum of the thicknesses of the layers constituting the anti-reflection layer (total thickness).
[0096] (Method for Forming Antireflection Layer 20)
[0097] The anti-reflection layer 20 is formed (film-formed) on, for example, the primer layer 25 by a wet coating method or a dry coating method. From the perspective of being able to form a thin film with uniform film thickness, a dry coating method such as a vacuum evaporation method, a CVD method, or a sputtering method is preferred. In addition, from the perspective of improving productivity, as a film-forming method for the anti-reflection layer 20, a roll-to-roll sputtering method is preferred. When the sputtering method is adopted, the film-forming conditions can be appropriately set, for example, in the conditions described in the above-mentioned (method for forming the primer layer 25).
[0098] [Antifouling layer 14]
[0099] The antifouling layer 14 is provided for the purpose of easily preventing pollution from the external environment and removing attached pollutants. In order to suppress the reduction of the antireflection performance of the antireflection layer 20, the refractive index difference between the antifouling layer 14 and the outermost layer (e.g., silicon oxide layer) of the antireflection layer 20 is preferably small. The refractive index of the antifouling layer 14 is preferably 1.6 or less, and more preferably 1.55 or less.
[0100] The antifouling layer 14, for example, contains a fluorine-containing compound having an end structure represented by the chemical formula CF3O- (specifically, CF3-O-). The fluorine-containing compound having an end structure represented by the chemical formula CF3O- has excellent antifouling properties and can contribute to a low refractive index. Among them, from the perspective of excellent hydrophobicity and high antifouling properties, the fluorine-containing compound is preferably an alkoxysilane compound containing a perfluoropolyether skeleton. As an alkoxysilane compound containing a perfluoropolyether skeleton, the compounds represented by the following general formula can be listed.
[0101] CF3-(OCF2) m -(OC2F4) n -O-(CH2)3-Si(OCH3)3
[0102] In the above general formula, m represents an integer of 1 to 51, and n represents an integer of 1 to 50.
[0103] In addition, the fluorine-containing compound having a terminal structure represented by the chemical formula CF3O- can be used alone or in combination of two or more. It should be noted that when the above-mentioned alkoxysilane compound is used as the fluorine-containing compound, the above-mentioned alkoxysilane compound can be present in the antifouling layer 14 in a state where the terminal alkoxy group has reacted (cross-linked).
[0104] The thickness of the antifouling layer 14 is, for example, 2 nm or more and 50 nm or less. There is a tendency that the antifouling property is improved as the thickness of the antifouling layer 14 increases. The thickness of the antifouling layer 14 is preferably 5 nm or more, more preferably 6 nm or more, and further preferably 7 nm or more. On the other hand, in order to further suppress the reflection of external light, the thickness of the antifouling layer 14 is preferably 30 nm or less, more preferably 20 nm or less, and further preferably 15 nm or less.
[0105] (Method for Forming Antifouling Layer 14)
[0106] The antifouling layer 14 is formed, for example, on the antireflection layer 20 by a wet coating method or a dry coating method. When a fluorine-containing compound is used as a material, in order to form a uniform film of the fluorine-containing compound, it is preferable to form the antifouling layer 14 by a dry coating method. Examples of the dry coating method include a vacuum evaporation method, a sputtering method, and a CVD method, and a vacuum evaporation method is preferable.
[0107] [Base material layer 16]
[0108] The substrate layer 16 is formed, for example, by any appropriate film. As the constituent material of the film, for example, polyester resins such as polyethylene terephthalate resins, polycycloolefin resins such as polynorbornene resins, polyolefin resins such as polypropylene, polyamide resins, polycarbonate resins, and copolymer resins thereof can be cited. In order to improve the hardness of the substrate layer 16, the constituent material of the substrate layer 16 is preferably a polyester resin. The thickness of the substrate layer 16 is, for example, greater than 10 μm and less than 200 μm, preferably greater than 20 μm and less than 150 μm. It should be noted that the substrate layer 16 may be a laminate of more than two layers. In the case where the substrate layer 16 is a laminate of more than two layers, for example, the substrate layer 16 may be a laminate having a film substrate and the above-mentioned layer containing a conductive polymer. As a film substrate provided with a layer containing a conductive polymer, a film formed of the material exemplified as the constituent material of the above-mentioned substrate layer 16 is preferably used.
[0109] [Adhesive layer 17]
[0110] The adhesive layer 17 is formed of, for example, any appropriate adhesive. Examples of the adhesive include (meth)acrylic adhesives, urethane adhesives, silicone adhesives, etc. The thickness of the adhesive layer 17 is, for example, 1 μm to 40 μm, preferably 2 μm to 30 μm.
[0111] In order to improve the transportability of the optical layered body 10 , the total thickness of the base layer 16 and the adhesive layer 17 (the thickness of the surface protection film 15 ) is preferably 15 μm to 150 μm, more preferably 20 μm to 100 μm.
[0112] [Preferred embodiment of optical layered body A]
[0113] In the present embodiment, in order to suppress the occurrence of poor pickup and touch panel sensor errors and reduce manufacturing costs, the optical laminate A preferably satisfies the following condition 1. In addition, in the present embodiment, in order to improve the antifouling performance of the antifouling layer while suppressing the occurrence of poor pickup and touch panel sensor errors and reducing manufacturing costs, the optical laminate A preferably satisfies the following condition 2, and more preferably satisfies the following condition 3.
[0114] Condition 1: The surface resistivity of the first main surface of the optical laminate A is 1.0×10 7 Ω / □ or more and 1.0×10 13 Ω / □ or less, and the surface resistivity of the second main surface of the optical laminate A is 1.0×10 8 Ω / □ or more and 1.0×10 13 Ω / □ or less.
[0115] Condition 2: The above-mentioned condition 1 is satisfied, and the antifouling layer is in contact with the surface protection film, and the water contact angle of the main surface of the antifouling layer on the surface protection film side is 100° or more.
[0116] Condition 3: The above-mentioned condition 2 is satisfied, and the water contact angle of the main surface of the antifouling layer on the surface protection film side is 125° or less.
[0117] [Other embodiments]
[0118] The optical laminate with a surface protection film of the present embodiment has been described above, but the present invention is not limited to the above-mentioned embodiment. For example, the optical laminate with a surface protection film of the present invention may not have a primer layer and an anti-reflection layer. In addition, the optical laminate with a surface protection film of the present invention may have an optical functional layer different from the layer included in the above-mentioned constitution.
[0119] In the optical layered body with a surface protection film of the present invention, the surface protection film may be composed of only one layer (substrate layer). A surface protection film composed of only a substrate layer has, for example, adhesiveness on one main surface.
[0120] [Example]
[0121] Hereinafter, examples of the present invention will be described, but the present invention is not limited to the following examples.
[0122] <Production of optical layered body of Example 1>
[0123] Hereinafter, a method for producing the optical layered body of Example 1 will be described. First, a method for producing an antireflection film will be described.
[0124] [Production of anti-reflection film]
[0125] (Hard Coat Layer Forming Step)
[0126] A photopolymerization initiator ("Omnirad907" manufactured by IGM Resins) and a leveling agent ("GRANDIC PC4100" manufactured by DIC) were added to a butyl acetate solution of an ultraviolet-curable urethane acrylate ("LUXYDIR17-806" manufactured by DIC Corporation, solid content concentration: 80% by weight). The amount of the photopolymerization initiator and the leveling agent added was 2.4 parts by weight and 0.1 parts by weight, respectively, relative to 100 parts by weight of the solid content in the butyl acetate solution of the above-mentioned urethane acrylate. The resulting mixture was diluted with a 1-methoxy-2-propanol / cyclopentanone mixed solvent (weight ratio 65 / 35) to obtain a hard coat layer forming composition H1 having a solid content concentration of 36% by weight. Next, the hard coat layer forming composition H1 was applied to one main surface of a TAC film ("KC8UA" manufactured by Konica Minolta Corporation, thickness: 80 μm) as a transparent film using Comma Coater (registered trademark) to form a coating film. Next, the coating film was dried by heating at 80°C for 60 seconds, and then cured by ultraviolet irradiation. During ultraviolet irradiation, a high-pressure mercury lamp was used as a light source, ultraviolet rays with a wavelength of 365 nm were used, and the cumulative light intensity was set to 300 mJ / cm 2 Thus, a transparent film substrate having a TAC film and a hard coat layer (thickness: 6 μm) was obtained.
[0127] (Surface modification process of hard coating)
[0128] Next, a TAC film (transparent film substrate) with a hard coating layer formed thereon was transported in a vacuum atmosphere of 0.5 Pa using a roll-to-roll plasma treatment device while the surface of the hard coating layer was subjected to plasma treatment. During the plasma treatment, argon gas was used as an inert gas, and the effective power density was set to 0.02 W·min / cm 2 m. Thus, a laminate having a TAC film and a hard coat layer treated with plasma (hereinafter sometimes referred to as "optical film F1") was obtained. It should be noted that the effective power density refers to the power density (W / cm 2 ) divided by the film conveying speed (m / min) in the roll-to-roll method.
[0129] Next, the primer layer forming process and the anti-reflection layer forming process are described. It should be noted that in the primer layer forming process and the anti-reflection layer forming process, when the oxide film is formed (film-forming), argon gas and oxygen are introduced into the film forming chamber while the film is formed. In addition, when the oxide film is formed (film-forming), the pressure is kept constant by adjusting the introduction amount and exhaust amount of argon gas, and the introduction amount of oxygen is adjusted in a manner to maintain the transition region in the film forming mode through plasma emission monitoring (PEM) control.
[0130] (Primer layer forming step)
[0131] The optical film F1 obtained in the above steps was introduced into a roll-to-roll sputtering film forming apparatus, and the pressure in the film forming chamber was reduced to 1×10 -4 Pa. Next, while the optical film F1 was conveyed, the surface temperature of the film-forming roller was set to -8°C, and a 3 nm thick SiOx layer (x < 2) was formed as a primer layer on one main surface of the hard coat layer by reactive sputtering. In forming the primer layer, a Si target was used as a target material.
[0132] (Anti-reflection layer forming step)
[0133] After the formation of the primer layer, a roll-to-roll sputtering film forming device was used to transport the optical film F1 after the primer layer was formed while forming films on one main surface of the primer layer by reactive sputtering: the first layer: a niobium oxide layer with a thickness of 10.1 nm (refractive index: 2.33), the second layer: a silicon oxide layer with a thickness of 27.5 nm (refractive index: 1.46), the third layer: a niobium oxide layer with a thickness of 105.0 nm, and the fourth layer: a silicon oxide layer with a thickness of 83.5 nm. It should be noted that a Si target was used for the formation of the silicon oxide layer, and a Nb target was used for the formation of the niobium oxide layer. Thus, an anti-reflection layer having a four-layer structure (four-layer structure consisting of the first layer, the second layer, the third layer, and the fourth layer) was formed on one main surface of the primer layer.
[0134] (Antifouling layer forming step)
[0135] A coating agent ("SHIN-ETSU SUBELYN KY1903-1" manufactured by Shin-Etsu Chemical Co., Ltd., active ingredient: alkoxysilane compound containing a perfluoropolyether skeleton) was dried and solidified as a vapor deposition source, and the heating temperature of the vapor deposition source was set to 260°C. An antifouling layer with a thickness of 8 nm was formed on the antireflection layer by vacuum vapor deposition. Thus, an antireflection film AR1 having a TAC film, a hard coat layer, a primer layer, an antireflection layer, and an antifouling layer in this order was obtained.
[0136] [Production of surface protection film]
[0137] (Process for preparing conductive polymer-containing treatment agent)
[0138] First, an aqueous solution containing 0.5 wt% of poly(3,4-ethylenedioxythiophene) as a conductive polymer and 0.8 wt% of polystyrene sulfonic acid (number average molecular weight: 150,000) ("Clevios P" manufactured by Heraeus, hereinafter referred to as "conductive polymer aqueous solution CA1") was prepared. In addition, an aqueous dispersion containing 25 wt% of a saturated copolyester resin as a binder ("Vylonal MD-1480" manufactured by Toyobo Co., Ltd., hereinafter referred to as "binder dispersion BD1") was prepared. In addition, an aqueous dispersion containing 8.0 wt% of carnauba wax as a slip-imparting agent was prepared (hereinafter referred to as "slip-imparting agent dispersion SD1"). Then, in a mixed solvent containing water and ethanol in a volume ratio of 1:1, 100 parts by weight of the above-mentioned adhesive dispersion BD1, 40 parts by weight of the above-mentioned slip imparting agent dispersion SD1, 50 parts by weight of the above-mentioned conductive polymer aqueous solution CA1, and 10 parts by weight of a melamine-based cross-linking agent were added, and stirred and mixed for 20 minutes to prepare a conductive polymer-containing treatment agent CP1 with a solid content concentration of 0.3% by weight.
[0139] (Base material layer formation step)
[0140] The conductive polymer-containing treatment agent CP1 was applied to one side of a PET film having a thickness of 38 μm by a bar coater, and the conductive polymer-containing treatment agent CP1 was dried by heating at a temperature of 130° C. for 30 seconds. Thus, a conductive polymer-containing layer having a thickness of 40 nm was formed on one side of the PET film, and a base material layer having a two-layer structure in which a conductive polymer-containing layer was laminated on the PET film was obtained.
[0141] (Adhesive Layer Formation Step)
[0142] First, an adhesive composition PS1 was prepared. Specifically, 96 parts by weight of 2-ethylhexyl acrylate as monomer components, 4 parts by weight of 2-hydroxyethyl acrylate, 0.2 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator, and 150 parts by weight of ethyl acetate were added to a reaction container equipped with a thermometer, a stirrer, a cooler, and a nitrogen inlet pipe, and nitrogen gas was introduced to perform nitrogen substitution while the container contents were maintained at a temperature of 23°C and stirred. Thereafter, the temperature of the container contents was maintained at 65°C, and a polymerization reaction was performed for 6 hours to obtain an acrylic polymer solution (concentration: 40% by weight). To 250 parts by weight of the obtained acrylic polymer solution, 73 parts by weight of toluene and 10 parts by weight of acetylacetone were added, and further 5.3 parts by weight of an ethyl acetate solution containing 75% by weight of a toluene diisocyanate trimer adduct of trimethylolpropane ("Coronate L" manufactured by Tosoh Corporation) and 4 parts by weight of a solution containing 0.5% by weight of a dioctyltin dilaurate catalyst ("EMBILIZER OL-1" manufactured by Tokyo Fine Chemical Co., Ltd.) were added and stirred to obtain an adhesive composition PS1.
[0143] Next, the adhesive composition PS1 was applied to one side of the PET film of the substrate layer (specifically, the main surface of the PET film opposite to the side of the layer containing the conductive polymer), and the adhesive composition PS1 was dried by heating at a temperature of 130° C. for 2 minutes. Thus, an adhesive layer with a thickness of 23 μm was formed on one side of the PET film, and a surface protection film SP1 was obtained. Then, in order to protect the adhesive layer, a release-treated surface of a release-treated film (MRF38 manufactured by Mitsubishi Chemical Co., Ltd., a PET film with a release treatment on one side) with a thickness of 38 μm was attached to the exposed surface of the adhesive layer.
[0144] [Production of release liner]
[0145] (Step of forming a layer containing a conductive polymer)
[0146] The conductive polymer-containing treatment agent CP1 was applied to one side of a PET film having a thickness of 75 μm by a bar coater, and the conductive polymer-containing treatment agent CP1 was dried by heating at a temperature of 130° C. for 30 seconds. Thus, a conductive polymer-containing layer having a thickness of 45 nm was formed on one side of the PET film, and a laminate L1 in which a conductive polymer-containing layer was laminated on a PET film was obtained.
[0147] (Release treatment process)
[0148] First, a release treatment agent RP1 was prepared. Specifically, 30 parts by weight of a non-fluorine-based addition-type silicone composition containing a polyorganosiloxane having a hexene group ("LTC761" manufactured by DuPont Toray Specialty Materials), 0.9 parts by weight of a SILICONE DISPERSION ("BY 24-850" manufactured by DuPont Toray Specialty Materials), and 2 parts by weight of a platinum catalyst for silicone curing ("SRX 212" manufactured by DuPont Toray Specialty Materials) were diluted with a mixed solvent containing toluene and hexane in a volume ratio of 1:1 to prepare a release treatment agent RP1 having a silicone concentration of 1% by weight.
[0149] Next, the release agent RP1 was applied to the main surface of the laminate L1 opposite to the conductive polymer-containing layer side by a bar coater, and the release agent RP1 was dried by heating at 130° C. for 1 minute. Thus, one main surface of the laminate L1 was release treated to obtain a release liner RL1.
[0150] [Production of Release Liner with Adhesive Layer]
[0151] (Adhesive composition preparation process)
[0152] After a monomer mixture of 60 parts by weight of butyl acrylate, 6 parts by weight of cyclohexyl acrylate, 26 parts by weight of 4-hydroxybutyl acrylate, and 8 parts by weight of 2-hydroxyethyl acrylate was placed in a four-necked flask, 0.09 parts by weight of 2,2-dimethoxy-2-phenylacetophenone ("Omnirad651" manufactured by IGM Resins) and 0.09 parts by weight of 1-hydroxycyclohexyl-benzophenone ("Omnirad184" manufactured by IGM Resins) were placed in the above four-necked flask, and the contents of the flask were irradiated with ultraviolet rays under a nitrogen atmosphere to obtain a partial polymer (monomer syrup) with a polymerization rate of 10% by partial photopolymerization. To 100 parts by weight of the partial polymer were added 0.12 parts by weight of dipentaerythritol hexaacrylate ("KAYARAD DPHA" manufactured by Nippon Kayaku Co., Ltd.) and 0.3 parts by weight of 3-glycidoxypropyltrimethoxysilane ("KBM-403" manufactured by Shin-Etsu Chemical Co., Ltd.) as polyfunctional polymerizable compounds, and these were mixed to obtain an adhesive composition PS2.
[0153] (Adhesive Layer Formation Step)
[0154] After the adhesive composition PS2 was applied to the release treated surface of the release liner RL1 to form a coating layer formed of the adhesive composition PS2, the release treated surface of a release treated film (MRF38 manufactured by Mitsubishi Chemical Co., Ltd.) with a thickness of 38 μm was attached to the coating layer. 2 And the accumulated light intensity is 3600mJ / cm 2 The pressure-sensitive adhesive layer in the release liner PRL1 having the release liner RL1, the pressure-sensitive adhesive layer and the release treatment film in this order was irradiated with ultraviolet rays under the conditions of . The pressure-sensitive adhesive layer in the release liner PRL1 having the pressure-sensitive adhesive layer had a thickness of 25 μm.
[0155] [Lamination of surface protection film and release liner]
[0156] After peeling off the release treatment film (MRF38 manufactured by Mitsubishi Chemical Co., Ltd.) from the surface protection film SP1, the adhesive layer of the surface protection film SP1 was bonded to the surface of the antifouling layer of the antireflection film AR1 using a roll laminator. Next, after peeling off the release treatment film (MRF38 manufactured by Mitsubishi Chemical Co., Ltd.) from the adhesive layer of the release liner PRL1 with an adhesive layer, the exposed surface of the adhesive layer was bonded to the main surface (main surface of the TAC film) of the antireflection film AR1 on the opposite side to the surface protection film SP1 side using a roll laminator, thereby obtaining the optical laminate of Example 1.
[0157] <Production of optical layered body of Example 2>
[0158] An optical layered body of Example 2 was obtained in the same manner as in Example 1 except that release liner RL2 was used instead of release liner RL1. Release liner RL2 was produced in the same manner as in the production method of release liner RL1 except that the thickness of the conductive polymer-containing layer was changed to 10 nm.
[0159] <Production of optical layered body of Example 3>
[0160] The optical laminate of Example 3 was obtained by the same method as Example 1 except that the surface protection film SP2 was used instead of the surface protection film SP1. The surface protection film SP2 was prepared by the same method as the preparation method of the surface protection film SP1 except that the treatment agent CP2 containing a conductive polymer was used instead of the treatment agent CP1 containing a conductive polymer and the thickness of the layer containing the conductive polymer was changed to 30 nm. The treatment agent CP2 containing a conductive polymer was prepared by the same method as the preparation method of the treatment agent CP1 containing a conductive polymer except that the amount of the conductive polymer aqueous solution CA1 added was changed to 80 parts by weight in terms of solid content.
[0161] <Production of optical layered body of Example 4>
[0162] An optical layered body of Example 4 was obtained in the same manner as in Example 1 except that surface protection film SP3 was used instead of surface protection film SP1. Surface protection film SP3 was produced in the same manner as in the production method of surface protection film SP1 except that the thickness of the conductive polymer-containing layer was changed to 10 nm.
[0163] <Preparation of Optical Laminated Body of Comparative Example 1>
[0164] An optical layered body of Comparative Example 1 was obtained in the same manner as in Example 1 except that release liner RL3 was used instead of release liner RL1. Release liner RL3 was produced in the same manner as in the production method of release liner RL1 except that a conductive polymer-containing layer was not provided.
[0165] <Preparation of optical layered body of Comparative Example 2>
[0166] An optical layered body of Comparative Example 2 was obtained in the same manner as in Example 1 except that release liner RL4 was used instead of release liner RL1. Release liner RL4 was produced in the same manner as in the production method of release liner RL1 except that the thickness of the conductive polymer-containing layer was changed to 5 nm.
[0167] <Preparation of optical layered body of Reference Example 1>
[0168] An optical laminate of Reference Example 1 was obtained by the same method as in Example 1 except that a primer layer, an antireflection layer, and an antifouling layer were not formed and that a surface protection film SP1 was bonded to the hard coat layer side of the optical film F1.
[0169] <Measurement method and evaluation method>
[0170] Hereinafter, the measuring method and the evaluation method of the physical properties of each optical layered body will be described. In the following description concerning Reference Example 1, the "antifouling layer" is replaced by the "hard coat layer".
[0171] [Water contact angle]
[0172] First, using a contact angle measuring device ("DMo-701" manufactured by Kyowa Interface Science Co., Ltd.), 5.0 μL of water was dropped onto the antifouling layer surface (the main surface to which the surface protective film was attached) of each optical laminate before the surface protective film was attached. Next, 2 seconds after the droplet was added, the angle between the antifouling layer surface and the tangent line at the end of the droplet was measured.
[0173] [Sealing strength]
[0174] Each optical laminate was cut into a size of 50 mm in width and 100 mm in length, and after standing for 30 minutes under a standard environment, the release liner was peeled off, and the exposed adhesive layer was bonded to an acrylic plate to obtain a test sample. Next, the surface protective film at one end of the test sample in the longitudinal direction was peeled off, and a peeling test was performed under the conditions of a peeling angle of 180° and a tensile speed of 0.3 m / min, and the obtained peel strength was used as the adhesion strength (unit: N / 50 mm).
[0175] [Surface resistivity]
[0176] Under standard conditions, a resistivity meter ("Hiresta UP MCP-HT450" manufactured by Nitto Seiko Analytech Co., Ltd.) was used to contact the surface of the release liner or surface protective film of each optical laminate (the first main surface or the second main surface of the optical laminate) with the measuring terminal, and the surface resistivity was measured under the conditions of applying a voltage of 10 V and a voltage application time of 30 seconds. It should be noted that when the measurement could not be performed under the applied voltage of 10 V, the applied voltage was changed to 100 V to measure the surface resistivity.
[0177] [Pickup]
[0178] First, two samples of the optical laminates of Examples 1 to 4, Comparative Examples 1, Comparative Examples 2, and Reference Example 1 were cut into 15 cm × 30 cm pieces. Next, the two samples (specifically, each of the optical laminates of Examples 1 to 4, Comparative Examples 1, Comparative Examples 2, and Reference Example 1) were cut into 15 cm × 30 cm pieces. Figure 2 As shown below, Figure 2In the embodiment, the optical laminate located at the top is referred to as "optical laminate A1", and the optical laminate located at the bottom is referred to as "optical laminate A2". When the optical laminate A1 and the optical laminate A2 are superimposed, they are superimposed in such a way that the first principal surface A1a of the optical laminate A1 and the first principal surface A2a of the optical laminate A2 both become the surface of the release liner. Therefore, the second principal surface A1b of the optical laminate A1 and the second principal surface A2b of the optical laminate A2 are both the surfaces of the surface protection film.
[0179] Next, after sticking double-sided tape (not shown) between the left and right index fingers, the exposed surface of the double-sided tape was stuck to both ends of the optical laminate A1. Next, the pick-up property when picking up the both ends of the optical laminate A1 was evaluated based on the following criteria.
[0180] (Criteria for Pickup Performance)
[0181] A: The adhesion between the release liner of the optical layered body A1 and the surface protective film of the optical layered body A2 was low, and only the optical layered body A1 could be picked up.
[0182] B: Both the optical layered body A1 and the optical layered body A2 are picked up together, or the surface protection film is peeled off from the antifouling layer of the optical layered body A2.
[0183] When the pickup property was determined as A, it was evaluated as “the pickup property was excellent and the pickup failure was suppressed.” On the other hand, when the pickup property was determined as B, it was evaluated as “the pickup property was poor and the pickup failure was not suppressed.”
[0184] [Touch operability]
[0185] After peeling the release liner from each optical layered body, the exposed pressure-sensitive adhesive layer was bonded to the screen of "iPad (registered trademark) Air" manufactured by Apple Inc. to obtain an evaluation sample. Next, the surface of the surface protection film of the evaluation sample was touched, and the touch operability was determined according to the following criteria.
[0186] (Criteria for judging touch operability)
[0187] A: Touch operation is smooth.
[0188] B: Touch operation cannot be detected (touch operation is not possible).
[0189] If the touch operability is determined as A, it is evaluated as "excellent touch operability and touch panel sensor errors can be suppressed." On the other hand, if the touch operability is determined as B, it is evaluated as "poor touch operability and touch panel sensor errors cannot be suppressed."
[0190] <Results>
[0191] The water contact angle, adhesion strength, details of the release liner used, details of the surface protection film used, the results of the pick-up properties, and the results of the touch operability properties of the optical laminates of Examples 1 to 4, Comparative Examples 1, 2, and Reference Example 1 are shown in Table 1. In Table 1, “-” means that the surface resistivity exceeds 1.00×10 14 Ω / □.
[0192] [Table 1]
[0193]
[0194] As shown in Table 1, in Examples 1 to 4, the surface resistivity of the first main surface and the second main surface of the optical laminate was 1.0×10 13 Ω / □ or less. In Examples 1 to 4, the pickup properties were determined to be A. Therefore, the optical layered bodies of Examples 1 to 4 were excellent in pickup properties, and the occurrence of pickup failure was suppressed.
[0195] As shown in Table 1, in Comparative Examples 1 and 2, the surface resistivity of the first main surface of the optical laminate exceeded 1.0×10 13 Ω / □. In Comparative Examples 1 and 2, the pickup properties were determined to be B. Therefore, the pickup properties of the optical layered bodies of Comparative Examples 1 and 2 were poor, and the occurrence of pickup failure could not be suppressed.
[0196] The above results show that, according to the present invention, it is possible to provide an optical layered body with a surface protection film in which the occurrence of pickup failure can be suppressed.
Claims
1. An optical laminate with a surface protective film, comprising a release liner, an adhesive layer, a transparent film substrate, an antifouling layer and a surface protective film in this order, The main surface of the release liner opposite to the adhesive layer side is the first main surface of the optical laminate with a surface protection film. The main surface of the surface protection film opposite to the antifouling layer side is the second main surface of the optical laminate with a surface protection film. The surface resistivity of the first main surface and the second main surface of the optical laminate with a surface protection film is 1.0×10 13 Ω / □ or less.
2. The optical laminate with a surface protection film according to claim 1, wherein The antifouling layer is in contact with the surface protection film, The water contact angle of the main surface of the antifouling layer on the surface protection film side is 100° or more.
3. The optical laminate with a surface protection film according to claim 1, wherein The antifouling layer is in contact with the surface protection film, The adhesion strength between the antifouling layer and the surface protection film is 0.07 N / 50 mm or less.
4. The optical laminate with a surface protection film according to claim 1, wherein The surface resistivity of the second main surface of the optical laminate with a surface protection film is 1.0×10 8 Ω / □ or more.
5. The optical laminate with a surface protection film according to claim 1, wherein The transparent film substrate includes a transparent film and a hard coating layer provided on a first main surface side of the transparent film. The pressure-sensitive adhesive layer is provided on the second main surface side of the transparent film.
6. The optical laminate with a surface protection film according to claim 1, wherein The invention further comprises an antireflection layer provided between the transparent film substrate and the antifouling layer.
7. The optical laminate with a surface protection film according to claim 6, wherein The invention further comprises a primer layer provided between the transparent film substrate and the antireflection layer.
Citation Information
Patent Citations
Laminated plastic film for optical filter
JP2008151996A
Transparent conductive film and method for manufacturing the same
JP2016179686A